Testing genotoxicity and cytotoxicity strategies for the evaluation of commercial radiosterilized fetal calf sera - Pilili, Juan Pablo (2010)
Effects of 18 commercial lots of fetal calf serum (FCS) after γ-irradiation and their non-irradiated counterparts were comparatively analyzed on CHO-K1 and MDBK MDL1 cells for genotoxicity [sister chromatid exchange (SCE), micronuclei (MNi), and single cell gel electrophoresis (SCGE)], cytotoxicity [cell-cycle progression (CCP), proliferative replication index (PRI), mitotic index (MI), growth promotion (GP), and plating efficiency (PE)], and microbiological properties (mycoplasma and bovine viral diarrhea virus contamination). SCE and SCGE were the most informative end-points for genotoxicity since significant differences were found in 44.4% (P < 0.05-0.001, Student's t-test) and 61.1% (P < 0.05-0.001, χ2 test) samples, respectively. MI was the cytotoxicity assay revealing the greatest variation, showing differences in 66.7% (P < 0.05-0.001, χ2 test) samples. Thus, these three end-points for screening bioproducts such as FCS were found most suitable for detecting potential geno-cytotoxicants in biological samples; their simultaneous use could be strongly recommended.